Bibliometric research - Haddow, Gaby (Tilde University Press, 2013)
Bibliometric research is concerned with aspects of communication, such as citations, journal articles and content. It applies quantitative methods to a body of literature to arrive at an understanding of the communication patterns, trends and networks occurring in that literature. Originating in positivist sociology, bibliometrics has developed its own laws and measurement techniques. Measures such as the impact factor and the h-index are key indicators which are applied in many bibliometric studies. An understanding of important indicators and how to design studies using citation, author and affiliation, and content analyses, will provide those new to the field with the knowledge and skills to undertake bibliometric research. In doing so, the researcher must be aware of important challenges, assumptions and limitations associated with bibliometric research.